ANALISIS PENGARUH PERPUTARAN PIUTANG DAN PERPUTARAN KAS TERHADAP LIKUIDITAS KOPERASI KARYAWAN BEHAESTEX GRESIK - jurnalpps pps; Ulil Luthfy Fahmi; Fatimah Riswati; Bambang Winarto (Prodi Magister Manajemen Universitas Wijaya Putra, 2020)
The purpose of this research was to describe the accounts receivable turnover, cash turnover and liquidity of the Behaestex Gresik Employee Cooperative. Then to identify and analyze the effect of simultaneous accounts receivable turnover and cash turnover on Behaestex Gresik Employee Cooperative liquidity, to know and analyze the effects of partial accounts receivable and cash turnover to the liquidity of the Behaestex Gresik Employee Cooperative and to declare receivable turnover has a dominant influence on the liquidity of the Behaestex Gresik Employee Cooperative. The type of research used is an explanatory type of research. Explanatory research is a study aimed at testing a theory or hypothesis to strengthen or even reject the theory or hypothesis of the results of existing research.The results of this study is simultaneously accounts receivable turnover and cash turnover do not significantly affect the Behaestex Gresik Employee Cooperative liquidity; and partially accounts receivable turnover and cash turnover do not significantly affect the Behaestex Gresik Employee Cooperative liquidity, and the third influential receivable turnover dominant to the liquidity of the Behaestex Gresik Employee Cooperative.Keywords: accounts receivable turnover, cash turnover, liquidity